Maternal Morbidity during Childbirth Hospitalization in California - Lyndon, Audrey (2012)
OBJECTIVE: To determine the incidence and risk factors for maternal morbidity during childbirth hospitalization. METHODS: Maternal morbidities were determined using ICD9-CM and vital records codes from linked hospital discharge and vital records data for 1,572,909 singleton births in California, 2005-2007. Sociodemographic, obstetric, and hospital volume risk factors were estimated using mixed effects logistic regression models. RESULTS: The maternal morbidity rate was 241/1000 births. The most common morbidities were episiotomy, pelvic trauma, maternal infection, postpartum hemorrhage, and severe laceration. Preeclampsia (Adjusted Odds Ratio [AOR] 2.96; 95% CI 2.8,3.13), maternal age over 35 years, (AOR 1.92; 1.79,2.06), vaginal birth after cesarean, (AOR 1.81; 1.47,2.23), and repeat cesarean birth (AOR 1.99; 1.87,2.12) conferred the highest odds of severe morbidity. Non-white women were more likely to suffer morbidity. CONCLUSIONS: Nearly one in four California women experienced complications during childbirth hospitalization. Significant health disparities in maternal childbirth outcomes persist in the United States.